Electrochemotherapy of Spinal Metastases Using Transpedicular Approach—A Numerical Feasibility Study. (10th May 2018) - Cindrič, Helena; Kos, Bor; Tedesco, Giuseppe; Cadossi, Matteo; Gasbarrini, Alessandro; Miklavčič, Damijan
Vertebral column is the most frequent site for bone metastases. It has been demonstrated in previous studies that bone metastases can be efficiently treated by electrochemotherapy. We developed a novel approach to treat spinal metastases, that is, transpedicular approach that combines electrochemotherapy with already established technologies for insertion of fixation screws in spinal surgery. In the transpedicular approach, needle electrodes are inserted into the vertebral body through pedicles and placed around the tumor. The main goal of our study was to numerically investigate the feasibility of the proposed treatment approach. Three clinical cases were used in this study—1 with a tumor completely contained within the vertebral body and 2 with tumors spread also to the pedicles and spinal canal. Anatomically accurate numerical models were built for all 3 cases, and numerical computations of electric field distribution in tumor and surrounding tissue were performed to determine the treatment outcome. Complete coverage of tumor volume with sufficiently high electric field is a prerequisite for successful electrochemotherapy. Close to 100% tumor coverage was obtained in all 3 cases studied. Two cases exhibited tumor coverage of >99%, while the coverage in the third case was 98.88%. Tumor tissue that remained untreated was positioned on the margin of the tumor volume. We also evaluated hypothetical damage to spinal cord and nerves. Only 1 case, which featured a tumor grown into the spinal canal, exhibited potential risk of neural damage. Our study shows that the proposed transpedicular approach to treat spinal metastases is feasible and safe if the majority of tumor volume is contained within the vertebral body. In cases where the spinal cord and nerves are contained within the margin of the tumor volume, a successful and safe treatment is still possible, but special attention needs to be given to evaluation of potential neural damage.